Imposition of Import Duty and Taxes in the Context of Importation of Medical Devices in terms of Basic Health Rights as Human Rights - Wahyu Andrianto; Fadhlan Zamzami Sitio; Atika Rizka Fajrina (SOEPRA, 2021)
ABSTRACT: The right to health is one of the human rights listed in the Universal Declaration of Human Rights as a basic right of every individual and is non-derogable. Post- amendment, Article 34 paragraph (3) of the 1945 Constitution mandates; "The state is responsible for the provision of adequate health care facilities and public services." Additionally, article 98 of the Health Act confirms that the Government is responsible for the supply of pharmaceutical and medical devices that are safe, beneficial, qualified, and affordable. However, to this day the government still imposes import duties and taxes for imported medical devices, even though 90.3 percent of domestic medical device demands are supplied by imported goods. Naturally, the imposition of import duties and PDRI for medical devices will impact in increasing the costs of procurement of medical devices. This study aims to analyze the correlation between the imposition of import duty tariffs as well as the PDRI of medical devices and the principle of fulfilling the basic health rights mandated by laws and regulations. Therefore, this research was conducted in a juridical-normative approach. This study was conducted within the limitation of secondary data. Tools of data collection were in the form of document studies and interviews. Based on the conducted study, the researchers concluded that the imposition of import duties and taxes on medical devices is not in line with the principles mandated by law, specifically in the aspect of qualified and affordable medical device supply. Therefore, this study suggests that the government should consider reassessing the regulation of import duty and tax rates of imports  for medical devices in order to fulfill access to health for everyone. Keywords: Import Duties, Basic Health Rights, Human RightsABSTRAK: Hak atas Kesehatan (right to health) merupakan bagian dari hak asasi manusia yang tercantum dalam Deklarasi Universal Hak Asasi Manusia sebagai hak dasar dari setiap individu dan tidak dapat dihilangkan. Setelah diamandemen, Pasal 34 ayat (3) Undang-Undang Dasar 1945 mengamanatkan bahwa; “Negara bertanggung jawab atas penyediaan fasilitas pelayanan kesehatan dan fasilitas pelayanan umum yang layak.” Kemudian, Pasal 98 Undang-Undang Kesehatan menegaskan bahwa Pemerintah bertanggung jawab atas sediaan farmasi dan alat kesehatan yang aman, bermanfaat, bermutu dan terjangkau. Meski begitu, hingga saat ini pemerintah masih mengenakan bea masuk dan PDRI terhadap alat kesehatan impor, padahal 90,3 persen kebutuhan alat kesehatan dalam negeri dipasok oleh barang impor.  Pengenaan bea masuk dan PDRI pada alat kesehatan akan berimbas pada bertambahnya biaya pengadaan alat kesehatan. Tulisan ini menganalisis korelasi antara pengenaan tarif bea masuk dan PDRI alat kesehatan tersebut dengan prinsip pemenuhan hak dasar kesehatan yang diamanatkan peraturan perundang–undangan, dengan pendekatan yuridis-normatif. Penelitian dilakukan dengan batasan penggunaan data sekunder dan alat pengumpulan data berupa studi dokumen dan wawancara. Berdasarkan studi yang dilakukan, peneliti menyimpulkan bahwa pengenaan bea masuk dan pajak impor terhadap alat kesehatan tidak sejalan dengan apa yang diperintahkan oleh undang-undang, bahwa sediaan alat kesehatan harus bermutu dan terjangkau. Oleh karena itu, penelitian ini menyarankan agar pemerintah berkenan meninjau ulang pengaturan tarif bea masuk dan PDRI terhadap alat kesehatan demi pemenuhan akses kesehatan untuk setiap orang.Kata kunci : Bea Masuk, Hak Dasar Kesehatan, Hak Asasi Manusia